Towards a "Unified Field Theory" of Uneven Development: Human Productive Subjectivity, Capital and the International. Issue 3 (3rd July 2018) - Charnock, Greig; Starosta, Guido
Abstract : This article puts labour, and its historically changing forms of existence, at the centre of the theorisation of uneven international development. It advocates a consciously dialectical approach that goes beyond significant limitations in historical-geographical materialism, and in the work of Neil Smith in particular. It argues, first, that geopolitical modes of explanation cannot be asserted on descriptive grounds, or in logical abstraction from the determinate content of social reproduction. It then argues that the critique of uneven development must focus on the material process Marx termed the "real subsumption of labour to capital" so as to analyse the transformation of the productive subjectivity of the international working class in contemporary capitalism. This transformation has today resulted in the contemporary form of a "new" international division of labour, the worldwide dynamics of which are mediated by a variety of specific national and regional forms of the capital accumulation process.